The Integration of Muhammadiyah Boarding School (MBS) Tahfidz Al Hidayah Wonopringgo Learning Model and Muhammadiyah Orphanage Wonopringgo, Pekalongan Regency - Fuad, Asfal; Setianto, Gigih (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The MBS Tahfid Al Hidayah Wonopringgo Islamic Boarding School is a modern formal education institution that has an excellent Al-Qur'an memorization program and has an integrated education curriculum with the Wonopringgo Muhammadiyah Middle School. In contrast to orphanages as social institutions whose curriculum administration has not been written neatly, Islamic boarding schools are better able to form children with noble morals. The importance of integrating Islamic boarding school education and orphanages can change the character of foster children who come to orphanages with various family, economic and character problems for the better, and have a mindset that foster children come to orphanages not only to fulfill economic needs, but more about change and the intention to gain the knowledge of memorizing the Koran. This research is qualitative research, descriptive in nature and uses analysis with an inductive approach. The results of this research show that foster children from orphanages live and participate integrally and comprehensively in activities at the Islamic boarding school with all the rules and discipline. The main activities of foster children in Islamic boarding schools are memorizing the Koran, formal schooling, cadre development, extracurricular activities and worship. The integration of Islamic boarding school education and orphanages increases the potential and achievements of foster children in memorizing the Al-Qur'an.